Various carboxylates induced eight Zn(ii)/Cd(ii) coordination polymers with fluorescence sensing activities for Fe(iii), Cr(vi) and oxytetracycline. Issue 46 (8th November 2021) - Chen, Yaxuan; Liu, Guocheng; Wang, Xiuli; Lu, Xue; Xu, Na; Chang, Zhihan; Zhang, Zhong; Li, Xiaohui
Abstract : Eight new Zn(ii )/Cd(ii ) coordination polymers constructed from a naphthalene-amide-pyridyl ligand and various carboxylates were synthesized and characterized, which show multifunctional fluorescence responses for cations, anions and antibiotics. Abstract : To study the effects of metal ions and various carboxylates on the assembly and structures of coordination polymers (CPs) based on a bis-pyridyl-bis-amide ligand [ N, N ′-bis(4-methylpyridine-4-yl)-2, 6-naphthalene dicarboxylamide] (4-bmnpd), eight Zn(ii ) and Cd(ii ) CPs, namely [Cd(4-bmnpd)(2-NBA)2 ] (1 ), [Cd(4-bmnpd)(3-NIP)(H2 O)] (2 ), [Cd2 (4-bmnpd)(TCPA)2 ] (3 ), [Cd(4-bmnpd)(5-HIP)(H2 O)] (4 ), [Cd(4-bmnpd)0.5 (5-MIP)(H2 O)] (5 ), [Cd3 O(4-bmnpd)(1, 4-PHDA)2 (H2 O)]·H2 O (6 ), [Zn(4-bmnpd)(5-MIP)] (7 ) and [Zn(4-bmnpd)(1, 2, 4, 5-BTA)0.5 ]·2H2 O (8 ) [2-HNBA = 2-nitrobenzoic acid, 3-H2 NIP = 3-nitrophthalic acid, H2 TCPA = tetrachlorophthalic acid, 5-H2 HIP = 5-hydroxyisophthalic acid, 5-H2 MIP = 5-methylisophthalic acid, 1, 4-H2 PHDA= 1, 4-phenylenediacetic acid and 1, 2, 4, 5-H4 BTA = 1, 2, 4, 5-benzenetetracarboxylic acid] were synthesized under hydrothermal conditions. CPs 1–8 were characterized by elemental analysis, IR and powder X-ray diffraction. Both CPs 1 and 2 are 2D networks. CP 3 shows a 2D 3, 4, 5-coordinated net based on binuclear nodes. CPs 4 and 5 are 2D lamellar structures with (4, 4) and (3, 4) topologically connected patterns, respectively. CP 6 is a 3D framework constructed from multi-member [Cd10 (1, 4-PHDA)4 ] n rhombus rings and 1D [Cd3 O2 ] n chains. CP 7 is a 1D ladder structure. CP 8 is a 2D structure extended by deprotonation of 1, 2, 4, 5-H4 BTA and 4-bmnpd linkers. The influence of the choice of metal as well as the carboxylic acid on the structures of the above CPs is discussed in detail. The fluorescence sensing properties of CPs 1–8 toward metal cations (Fe 3+ ), anions (CrO4 2−, Cr2 O7 2− ) and antibiotics (oxytetracycline) were investigated. The limits of detection for Fe 3+, CrO4 2−, Cr2 O7 2− and oxytetracycline were 6.9 × 10 −5 –1.5 × 10 −4, 6.9 × 10 −5 –1.3 × 10 −4, 7.7 × 10 −5 –1.3 × 10 −4, and 8.5 × 10 −5 –9.6 × 10 −4, respectively.